Arthur Andersen. (A), The waste management crisis - Diermeier, Daniel, (SAGE knowledge. Cases., 2016)
The cases describe the demise of Arthur Andersen, a firm that had long set the industry standard for professionalism in accounting and auditing. Once an example of strong corporate culture with a commitment to public service and independent integrity, Andersen saw its culture and standards weaken as it grew explosively and changed its mode of governance.